Surface Integrity Study of AISI 1045 Material in Dry Machining Using Coated Carbide Tool - Fransnazoan Sitorus; Irwansyah; Emil Salim P Siregar (LPPM Politeknik Aceh Selatan, 2023)
In metal cutting processes, the source of surface integrity deviation is a combination of several factors. The surface roughness parameter (Ra) is sufficient to determine the quality level of the surface packaging of a product, so it is widely used as a parameter to determine the surface packaging level of a product. Carbide tools dominate modern applications in the metalworking industry and are the preferred choice for metal cutting processes. Carbide tools can be improved through a coating process. In particular, the purpose of this study was to obtain surface roughness and optimum cutting conditions for dry machining of AISI 1045 materials using coated carbide tool when used in dry machining as well as for the development of research and development with research design analysis of the results of student practicum processes in laboratories, especially surface packaging material analysis. The material used is AISI 1045 with PVD TiAlN-TiN coated carbide tool. Combination machining process of cutting conditions, namely cutting speed, feed and depth of cut. Surface roughness test results on AISI 1045 test material with uncoated carbide tool surface roughness value = 9,042µm in cutting conditions: v= 235 m/min; f= 0.05mm/put; a=0.5mm; tc= 5.23 min. And the results of the surface roughness test on the AISI 1045 test material with PVD coated carbide tool with the best average surface roughness value = 6,135µm in cutting conditions: v=235 m/min; f=0.75 mm/put; a=1mm; tc=5.30 min.